Exploring the Expression of Cardiac Regulators in a Vertebrate Extremophile: The Cichlid Fish Oreochromis (Alcolapia) alcalica - Gemma Sutton; Lewis J. White; Antonia G.P. Ford; Asilatu Shechonge; Julia J. Day; Kanchon K. Dasmahapatra; Mary E. Pownall (Journal of Developmental Biology, 2020)
Although it is widely accepted that the cellular and molecular mechanisms of vertebrate cardiac development are evolutionarily conserved, this is on the basis of data from only a few model organisms suited to laboratory studies. Here, we investigate gene expression during cardiac development in the extremophile, non-model fish species, Oreochromis (Alcolapia) alcalica. We first characterise the early development of O. alcalica and observe extensive vascularisation across the yolk prior to hatching. We further investigate heart development by identifying and cloning O. alcalica orthologues of conserved cardiac transcription factors gata4, tbx5, and mef2c for analysis by in situ hybridisation. Expression of these three key cardiac developmental regulators also reveals other aspects of O. alcalica development, as these genes are expressed in developing blood, limb, eyes, and muscle, as well as the heart. Our data support the notion that O. alcalica is a direct-developing vertebrate that shares the highly conserved molecular regulation of the vertebrate body plan. However, the expression of gata4 in O. alcalica reveals interesting differences in the development of the circulatory system distinct from that of the well-studied zebrafish. Understanding the development of O. alcalica embryos is an important step towards providing a model for future research into the adaptation to extreme conditions; this is particularly relevant given that anthropogenic-driven climate change will likely result in more freshwater organisms being exposed to less favourable conditions.